Creative Language Games for Enjoyable Arabic Teaching l al-Al’ab al-Lughawiyyah al-Ibda'iyyah li Ta’lim al-Lughah al-'Arabiyyah al-Mumti'ah - Rahmawati, Fitra Awalia; Nur, Ifa Rodifah; Taqiyuddin, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2021)
Arabic teaching has the aim in the mastery of four skills; listening, speaking, reading, and writing. Considering to the languages teaching nowadays, educative games are commonly used as inseparable method from their curriculum. This method also had been practiced in Arabic teaching by some teachers. For this context, some rules need to be curricularly formulated. This critical point had not been elaborated curricularly. In this research, Library research model highlighted several studies of Arabic learning practices through game methods; then analyzed it with analytical and descriptive critical discourse methods to formulating the good, proper, and ideal ‘educative game’ in Arabic teaching. This study concluded the language game which emphasized some aspects such as 1) teacher competency, 2) facilities and infrastructure, 3) environmental conditions and situations. These three prerequisites are important in carrying out language teaching through ’curricular’ language games. Thus, educative language games can be formulated curricularly, which can be a simply contribution for practicing Arabic teaching through ‘educative games’.